PELATIHAN PEMBUATAN ALAT PERAGA PEMBELAJARAN MATEMATIKA SEDERHANA DI SD NEGERI 42 PALEMBANG - Ignasius Putera Setiahati; Lisnani; Ria Triayomi (Jurnal Abdimas Musi Charitas, 2018)
Mathematics is a special discipline that is often considered a difficult discipline by many people. Many people are afraid and try to avoid math. Mathematics requires special methods and tools so that math is interesting and not scary and students can achieve maximum and high quality learning outcomes. One of those tools is an instructional media that we call props. Basically, simple mathematical props do not have to buy and be expensive. Even elementary school children can be trained to make simple mathematical props so that their creativity is sharpened and math learning becomes more interesting. With experimental methods, lectures and discussions, children can be guided to make these simple mathematical props. It turns out that children can produce good props. Furthermore, mathematics lessons are more interesting and hope they master math with satisfying results.